Pancreatic β-cell hyper-O-GlcNAcylation leads to impaired glucose homeostasis in vivo - Jo, Seokwon; Pritchard, Samantha; Wong, Alicia; Avula, Nandini; Essawy, Ahmad; Hanover, John; Alejandro, Emilyn U. (Frontiers in Endocrinology, 2022)
Protein O-GlcNAcylation is a nutrient and stress-sensitive protein post-translational modification (PTM). The addition of an O-GlcNAc molecule to proteins is catalyzed by O-GlcNAc transferase (OGT), whereas O-GlcNAcase (OGA) enzymes are responsible for removal of this PTM. Previous work showed that OGT is highly expressed in the pancreas, and we demonstrated that hypo-O-GlcNAcylation in β-cells cause severe diabetes in mice. These studies show a direct link between nutrient-sensitive OGT and β-cell health and function. In the current study, we hypothesized that hyper-O-GlcNAcylation may confer protection from β-cell failure in high-fat diet (HFD)-induced obesity. To test this hypothesis, we generated a mouse model with constitutive β-cell OGA ablation (βOGAKO) to specifically increase O-GlcNAcylation in β-cells. Under normal chow diet, young male and female βOGAKO mice exhibited normal glucose tolerance but developed glucose intolerance with aging, relative to littermate controls. No alteration in β-cell mass was observed between βOGAKO and littermate controls. Total insulin content was reduced despite an increase in pro-insulin to insulin ratio in βOGAKO islets. βOGAKO mice showed deficit in insulin secretion in vivo and in vitro. When young animals were subjected to HFD, both male and female βOGAKO mice displayed normal body weight gain and insulin tolerance but developed glucose intolerance that worsened with longer exposure to HFD. Comparable β-cell mass was found between βOGAKO and littermate controls. Taken together, these data demonstrate that the loss of OGA in β-cells reduces β-cell function, thereby perturbing glucose homeostasis. The findings reinforce the rheostat model of intracellular O-GlcNAcylation where too much (OGA loss) or too little (OGT loss) O-GlcNAcylation are both detrimental to the β-cell.